2011
DOI: 10.1590/s1135-57272011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre actividad física diaria, actividad física en el patio escolar, edad y sexo en escolares de educación primaria

Abstract: Daily PA is higher in boys compared to girls across all age groups (six to eleven years old). On the other hand, recess PA was higher only in boys between nine and eleven years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
0
8
1
18
Order By: Relevance
“…These findings contrast with a study conducted in Spain which only found differences in PA when the ages were more distant, i.e. 6 vs. 11 years old in girls and children (boys and girls) (Escalante et al, 2011). It should be noted, however, that the present study carried out in rural Welsh schools found levels of playground PA well above those of the Spanish schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings contrast with a study conducted in Spain which only found differences in PA when the ages were more distant, i.e. 6 vs. 11 years old in girls and children (boys and girls) (Escalante et al, 2011). It should be noted, however, that the present study carried out in rural Welsh schools found levels of playground PA well above those of the Spanish schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
“…Measurements made with it have been demonstrated to be strongly correlated with those of a triaxial accelerometer (Eisenmann et al, 2004). The method is similar to that followed in other studies (Escalante et al, 2011; Escalante et al, 2012; Kimm et al, 2000; Sigmund et al, 2009; Saglam et al, 2010). …”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…De la misma manera, Escalante determinó que su población masculina se mostró más competitiva, a diferencia de la femenina que prefirió actividades de carácter cooperativo y ven la hora del recreo como una oportunidad para socializar con los amigos (7,13). Por tanto, se infiere que el género femenino en estas edades podría estar realizando menor actividad física, predisponiéndolas a un estilo de vida sedentario en sus años posteriores.…”
Section: Discussionunclassified